Position-by-position cooling paths within the Toki granite, central Japan: Constraints and the relation with fracture population in a pluton. (January 2019) - Yuguchi, Takashi; Sueoka, Shigeru; Iwano, Hideki; Izumino, Yuya; Ishibashi, Masayuki; Danhara, Tohru; Sasao, Eiji; Hirata, Takafumi; Nishiyama, Tadao
Graphical abstract: Highlights: Position-by-position t-T paths are reconstructed from thermochronological data. Position-specific t-T paths reflect the formation history of the pluton. It is a new method for understanding of fracture populations in granite. The t-T path evaluation provides key insight to investigate fracture frequency. Abstract: Understanding the locational differences of time-temperature ( t-T ) paths within the granite contributes to clarifying the detailed formation history, especially the thermal evolution, of the entire pluton after the incipient intrusion of the granitic magma into the shallow crust. The position-by-position t-T paths of fifteen samples of the Toki granitic pluton, central Japan, are reconstructed from thermochronological data, including zircon U–Pb, biotite K–Ar, zircon fission-track (ZFT), and apatite fission-track (AFT) ages, FT length characterization, and FT inverse calculation. In case of sample No. 1, the t-T path consists of zircon U–Pb ages (74.0 ± 1.1 Ma and 72.6 ± 1.7 Ma), a biotite K–Ar age (73.0 ± 1.8 Ma), a ZFT age (57.2 ± 2.3 Ma), an AFT age (41.5 ± 2.7 Ma), and the FT inverse calculation. The t-T paths show position-specific characteristics that reflect the history of the pluton after the incipient intrusion of the granitic magma into the shallow crust. Shallow parts of the western and northeastern margins of the pluton show rapid cooling from the intrusion stage to the ZFT partial annealing zone (PAZ), and thus represent position-specific characteristics in relation to crustal assimilation in the intrusion/emplacement processes. The cooling behavior around the condition of AFT PAZ was interpreted as a reflection of regional tectonic exhumation of the pluton. This study also presents useful knowledge to evaluate fracture populations in a granitic pluton. The relationship between the position-specific t-T path and fracture frequency (fracture number per unit interval) provides a criterion for evaluating the fracture population of the granitic pluton, called 'thermochronological evaluation', which is a key insight to investigating fluid flow and mass transfer in the rock mass. The t-T path shows whether cooling was slow or rapid from thermal conditions of solidification/crystallization to the biotite K–Ar closure temperature; parts of the pluton that cooled slowly correspond to parts with high frequencies of fractures, and vice versa. The absolute value for duration between the zircon U–Pb age evaluated from the oscillatory-zoned area (OZ age) and biotite K–Ar age shows high correlation with fracture frequency ( R 2 = 0.89), and thus gives a quantitative indicator for evaluating fracture frequency; longer duration accompanies higher frequency. A combination of thermochronological evaluation, the local cooling indicator, and the lithofacies effect can be applied as potential diagnostic tools for detailed evaluation of the fracture population.